Analisis Prediksian Rasio Keuangan Terhadap Perubahan Laba pada Perusahaan Property dan Real Estate yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2008-2011 - Annisa Erselina; Ria Nelly Sari; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the research was to obtain empirical proof about the influence of the Current Ratio (CR) to changes a company's profits, gain empirical proof about the influence of Total Asset Turnover (TAT) to changes a company's profits, gain empirical proof about the effect of the Debt to Equity Ratio (DER) to changes a company's profits, gain empirical proof about the influence of Return on Assets (ROA) to changes a company's profits.The population in this research is all property and real estate company listed on the Stock Exchange from 2008 to 2011. Companies that meet the criteria and be sampled as many as 25 companies. Analysis of the research on the use of is using multiple linear regression equation with the help of software SPSS (Statistical Product and Service Solutions).Based on the t test showed that there is a partially significant effect of CR on Profit Growth in Property and Real Estate company. Based on the t test showed that there is no partial significant effect between Earnings Growth tattoo on the company's Property and Real Estate. Based on the t test showed that there is no partial significant influence of DER on Profit Growth in Property and Real Estate company. Based on the t test showed that there is a partially significant effect of ROA on Profit Growth in Property and Real Estate company. Based on the calculation of coefficient of determination (R2) of 0.320. This suggests that CR, TATO, DER, and ROA simultaneously giving effect to the 32% profit growth.Keywords: CR, TATO, DER, ROA and Profit Growth